Deruan Ombak: a musical journey through inspiration and process / Alia Farahin Abd Wahab, Khairunnisa Diyana Md Noor and Raja Mohamad Alif Raja Mohamad Adnan - Abd Wahab, Alia Farahin; Md Noor, Khairunnisa Diyana; Raja Mohamad Adnan, Raja Mohamad Alif (Faculty of Information Management, 2023)
"Deruan Ombak" is a musical composition that draws its inspiration from the melodic calls of birds in the lush forests of Bukit Sapu Tangan and Bukit Saga, Malaysia. Composed to capture the captivating sounds of these avian creatures, the composition is rooted in the lyrical richness of the Malaysian forest. The core of this research is a detailed analysis of the composition's structure, harmony, rhythm, and thematic elements. Furthermore, it seeks to enlighten the profound influence of the natural environment on the artistic process. "Deruan Ombak" serves as a sonic vessel to bridge the gap between human creativity and the natural world, inviting listeners to appreciate the intricate harmony that exists between the avian soundscape and human creativity. By exploring the intersection of music, literature, and ecology, this study invites readers to forge a deeper connection to the Malaysian landscape while appreciating the profound impact that artistry, inspired by the poetry of Siti Hajar Aznam, can have on environmental awareness.